2013
DOI: 10.1089/ham.2012.1109
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Skeletal Muscle Near Infrared Spectroscopy and a Vascular Occlusion Test at High Altitude

Abstract: Martin, Daniel, Denny Levett, Rick Bezemer, Hugh Montgomery, and Mike Grocott. The use of skeletal muscle near infrared spectroscopy and a vascular occlusion test at high altitude. High Alt Med Biol 14:256-262, 2013.-Microcirculatory function, central to tissue regulation of oxygen flux, may be altered by the chronic hypoxemia experienced at high altitude. We hypothesized that at high altitude, adaptations within skeletal muscle would result in reduced oxygen consumption and reduced microcirculatory responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
1
14
2
Order By: Relevance
“…Tissue Oxygenation Indexes measured from the forearm exhibited the expected drops in agreement with previous studies when NIRS was used in conjunction with vascular occlusions [29], [30] [8]- [10], [12], [20]- [23], [28]- [30]. The SpO2 only provides oxygen delivery information (i.e.…”
Section: B Hemoglobin Concentrationssupporting
confidence: 87%
See 1 more Smart Citation
“…Tissue Oxygenation Indexes measured from the forearm exhibited the expected drops in agreement with previous studies when NIRS was used in conjunction with vascular occlusions [29], [30] [8]- [10], [12], [20]- [23], [28]- [30]. The SpO2 only provides oxygen delivery information (i.e.…”
Section: B Hemoglobin Concentrationssupporting
confidence: 87%
“…The technique has been applied to measure cerebral and muscle perfusion, oxygen consumption, and blood flow in tissues. It also found applications in neonatal and foetal monitoring, somatic and splanchnic perfusion, peripheral vascular diseases, trauma medicine, sepsis, and plastic surgery [24]- [30].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our findings in skin are those of Treml et al (2018) using LDF, who found that lowlanders, on exposure to normobaric hypoxia, demonstrated a reduced hyperaemic response after occlusion. Moreover, reduced skeletal muscle microvascular reactivity has been demonstrated in lowlanders ascending to EBC using near-infrared spectroscopy (Martin, Levett, Bezemer, Montgomery, & Grocott, 2013). Clinically, impaired microvascular reactivity is seen in tissue hypoperfusion states, such as sepsis, and has been associated with worse clinical outcomes (Neviere et al, 1996).…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…The 'metabolic accumulation' sustained during the occlusion was determined as the integrated area under the curve (O-AUC) [20]. The reperfusion amplitude (R-AMP) was determined as the difference between the lowest and highest values achieved at the end of arterial occlusion and following cuff release, respectively [19,35]. The hyperemic response (HYP; CV = 16-20 %) was determined by the area under the curve following cuff release which was above resting values [23,35].…”
Section: Nirs Data Analysismentioning
confidence: 99%
“…The reperfusion amplitude (R-AMP) was determined as the difference between the lowest and highest values achieved at the end of arterial occlusion and following cuff release, respectively [19,35]. The hyperemic response (HYP; CV = 16-20 %) was determined by the area under the curve following cuff release which was above resting values [23,35]. Further, the increase in COLD was significantly greater than the increase in CON (p = 0.026, ES = 0.21) following 4 weeks of training.…”
Section: Nirs Data Analysismentioning
confidence: 99%